(untitled) (GEON Journal (Management, Organizations and Business), 2015)
The article presents the partial results of the characterization of international tourists up to Villavicencio, performing the assessment it makes the destination on expectations, satisfaction and evaluation. The data obtained while not conclusive, they do allow make a trend on the positioning that has Villavicencio internationally, helping to build the city brand and serves as a starting point to suggest strategies that make visible and strengthen the city. The methodology is quantitative and the data were processed through Excel and SPSS software. In general it can be inferred that the gratification of men supported by more concrete experiences, while women in the media is more abstract situations.